Impact of an Integrated Hip Fracture Inpatient Program on Length of Stay and Costs. Issue 12 (December 2016) - Soong, Christine; Cram, Peter; Chezar, Ksenia; Tajammal, Faiqa; Exconde, Kathleen; Matelski, John; Sinha, Samir K.; Abrams, Howard B.; Fan-Lun, Christopher; Fabbruzzo-Cota, Christina; Backstein, David; Bell, Chaim M.
Abstract : Background: Hip fractures are associated with significant morbidity and mortality. Co-management models pairing orthopaedic surgeons with hospitalists or geriatricians may be effective at improving processes of care and outcomes such as length of stay (LOS) and cost. We set out to determine the effect of an integrated hip fracture co-management model on LOS, cost, and process measures. Methods: We conducted a single-center pre–post study of 571 patients admitted to an academic medical center with hip fractures between January 2009 and December 2013. The group receiving an integrated medical-surgical co-management incorporating continuous improvement methodology was compared with a control population. Primary outcome was LOS. Secondary outcomes included cost per case, time to surgery, osteoporosis (OP) treatment, preoperative echocardiogram utilization, mortality, and readmission. Results: LOS decreased from 18.2 (1.1) to 11.9 (1.5) days, a reduction of 6.3 days ( P < 0.001). Mean cost decreased by $4953 ( P < 0.001) per case. Mean time to surgery decreased from 45.8 (66.8) to 29.7 (17.9) hours ( P < 0.001). Initiation of OP treatment increased from 55.8% to 96.4% ( P < 0.001). Preoperative echocardiogram use decreased from 15.8% to 9.1% ( P < 0.05). There was a nonsignificant difference in mortality rate (5.0% vs. 2.1%, P = 0.06). Readmission rate remained unchanged (4.6% vs. 6.0%, P = 0.56). Conclusions: An integrated medical-surgical co-management model incorporating continuous improvement methodology was associated with reduced LOS, costs, time to surgery, and increased initiation of appropriate OP treatment. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.